PENGARUH KECOCOKAN GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA INDIVIDU: STUDI KASUS PT. XYZ - Ignatius Jeffrey; Aji Hermawan; Musa Hubeis; Setiadi Djohar (Jurnal Manajemen & Agribisnis, 2011)
This study was designed to extend the Hersey and Blanchard's Situational Leadership Model to test the match of adaptability leadership style to the maturity level of subordinates using the LEAD-Self instrument and Readiness Scale of the Center for Leadership Studies. Maturity level of subordinate was analyzed based on the maturity level of employment (ability) and psychological maturity (willingness) to given work to subordinates. Also, to test compatibility with the leadership style with desired subordinates leadership style using LEAD-Other instrument. Leadership style is a combination of task behavior and behavioral relationships that will produce a directing coaching, participating delegating style. In addition, this study also tested the suitability of the existing organizational culture with the expectation organization culture. Effective matching leadership style and organizational culture is measured by the achievement of individual performance. The purpose of this study is to analyze the influence of matching between leadership style with the follower’s readiness level (X1), the leader's perceived leadership style with leader’s desired leadership style (X2), and the existing organizational culture with the expectation’s employees (X3) on the individual performance (Y1). The object of research was conducted at PT. XYZ and method of data retrieval is done by the census, while the method of analysis of this study was using the Structural Equation Modeling (SEM).   Keywords: Follower’s Readiness Level, Leader’s Perceived Leadership Style, Leader’s Desired Leadership Style, Existing and Expectation Culture, Individual Performance